HUMAN IMMUNODEFICIENCY VIRUS (HIV) PREVENTION PROGRAM AMONG MEN WHO HAVE SEX WITH MEN (MSM) IN SEMARANG CITY - Benita Noffritasari; Zahroh Shaluhiyah; M. Sakundarno Adi (Universitas Airlangga, 2020)
Background: The prevalence of Human Immunodeficiency Virus (HIV) among Men who have Sex with Men (MSM) in Indonesia continues to increase. The HIV cases among MSM in Semarang increased by 43 cases in 2013 to 147 cases in 2017. The prevalence of syphilis among MSM increased by 5.20% in 2011 to 11.38% in 2015. The use of condoms among MSM does not reach 50%. The Prevention of Sexual Transmission of HIV Program or Pencegahan HIV melalui Transmisi Seksual (PMTS) that focuses on sexual transmission risk factors did not provide optimal results.Aim: This study aimed to analyze aspects affecting the PMTS Program on MSM in Semarang City, including standard and objectives, resources, inter-organizational communication and enforcement activities, characteristics of the implementing agencies, economic, social, and political conditions, and the disposition of implementors.Method: This study was a descriptive study using a qualitative approach. Primary data were obtained through in-depth interviews with 14 informants, while secondary data were obtained from observation and document analysis. The data were analyzed using content analysis. The research was conducted from July to October 2019 in Semarang City.Results: The implemetation of the PMTS Program among MSM has some gaps. For example, these included (1) unclear standards of PMTS Program, (2) limited funding and infrastructures, (3) lack of communication, (4) stigma and discrimination at the stakeholder level, implementing agencies level, and community level.Conclusion: The implementation of PMTS Program among MSM has not worked appropriately. Eliminating stigma and discrimination against MSM needs to be taken into account. All health workers in primary healthcare centers must be introduced to the diminish of stigma and discrimination against MSM. Communication and coordination as well as resources among the program implementers have to be more well-established. Keywords: Human Immunodeficiency Virus, Men who have Sex with Men, prevention program.